PENGARUH KARTU KONTROL KESEHATAN GIGI DAN MULUT SEBAGAI UPAYA PENCEGAHAN KARIES GIGI PADA ANAK DI ERA NEW NORMAL DI SD NEGERI 2 BAUMATA TIMUR KABUPATEN KUPANG - Ferdinan Fankari; Emma Krisyudhanti (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2023)
The habit of brushing the teeth of the Indonesian people is still a cause for concern, as can be seen from the 2018 Basic Health Research data where only 2.3% of the population aged ≥ 10 years brush their teeth after breakfast and before going to bed at night. This condition can cause tooth decay, as seen from the Riskesdas data, where the tooth decay index (DMF-T) of the Indonesian population is 4.6, which means that every Indonesian resident has an average of 4-5 carious teeth. The high rate of dental caries is supported by the fact that the level of knowledge of the Indonesian people about the importance of brushing their teeth properly is still very low. The dental health control card is a medium for monitoring children's activities or behavior every day in carrying out routine toothbrushes in the morning after eating and at night before going to bed. This effort is expected to increase children's obedience in carrying out prevention efforts independently so that caries can be prevented. The purpose of this study was to determine the effect of dental and oral health control cards on efforts to prevent dental caries in children in the new normal era at SD Negeri 2 Baumata Timur, Kupang Regency. This research is an experiment with a one shot case study design, without a control group which was conducted on all 126 students of SDN 2 Baumata Timur. The results showed that the efforts to prevent dental caries before and after the intervention, the majority of students were in the very low category. The results of the Wilcoxon Signed Ranks Test showed a significant value of p 1.000 0.05 . The conclusion that there is no significant difference before and after treatment. It is recommended that there be education about the importance of consistency in brushing teeth for school-age children